Patrones de cobertura y protección de los bosques en el País Vasco - Gurrutxaga San Vicente, Mikel (Geographicalia, 2015)
There is analyzed how there are distributed the different types of natural forests in the Basque Country, with exception of the riparian ones, depending on the size of the wooded patches. Oak woods of Quecus robur stand out for they present a relative important surface in spots of small extension. There is analyzed the protection coverage of the Nature 2000 network on the different types of forests, being observed that oakwoods of Q. robur and Q. faginea, and pinewoods of Pinus sylvestris and P. halepensis, are those who present minor degree of coverage. These four types of forests are those that, in relative terms, major increase of surface they present when incorporate in the regional conservation network those sectors of the territorial matrix, called ecological corridors, with major aptitude to support the connectivity between protected forest areas.